2020
DOI: 10.1007/s12630-020-01825-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerosol box on intubation during COVID-19: a simulation study of normal and difficult airways

Abstract: Purpose Patients with coronavirus disease (COVID-19) are at risk of requiring mechanical ventilation, and concerns of protecting healthcare workers during aerosol-generating medical procedures has led to the design of the aerosol box. Methods We conducted a randomized crossover mannequin-based simulation study to compare airway management with and without the aerosol box. Thirty-five anesthesiology participants and three critical care participants with more than 50 intubations with videolaryngoscopes were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
3
20
0
3
Order By: Relevance
“…This corroborates the findings of other manikin studies ( 24 , 27 , 28 ). The median total intubation time in the aerosol box scenario was 30.9 s in our study, which is similar to that reported by Fong et al., but shorter than the time reported by Begley et al.…”
Section: Discussionsupporting
confidence: 92%
“…This corroborates the findings of other manikin studies ( 24 , 27 , 28 ). The median total intubation time in the aerosol box scenario was 30.9 s in our study, which is similar to that reported by Fong et al., but shorter than the time reported by Begley et al.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple factors, such as increased procedural difficulty, lack of experience, and cognitive overload for the proceduralist, may prolong TTI. 4 , 5 Although a mean delay of 4 s may seem negligible in the overall intubation time sequence, it is important to consider that simulated studies do not fully capture the influence human factors can play in real-life situations. This prolonged TTI should be considered in the context of critically ill patients with COVID-19, where risk of hypoxaemia can be higher, underpinning the importance of minimising apnoea time amongst these patients.…”
mentioning
confidence: 99%
“…A variety of barrier devices (e.g., cover box, or plastic tent) have been suggested to prevent aerosols and droplets from reaching the operator’s face 7 ; one third of respondents expressed being neutral and less than 50% seemed to agree/strongly agree with their use; although we do not know how many of respondents actually tried these devices, it is possible that most perceived the use of intubation boxes to be cumbersome in challenging cases, or that knowledge surrounding the fact that their manipulation may actually redirect aerosolized particles trapped under the shield had already emerged at the time of our survey. [8] , [9] , [10]…”
Section: Discussionmentioning
confidence: 99%